Physical fitness of students based on a test used to assess the physical fitness of soldiers of the National Reserve Forces - Pola Jalowska; Adam Prokopczyk (Physical Education of Students, 2022)
Background and Study Aim.  The purpose of this study was to analyze the physical fitness of students based on a test used to assess the physical fitness of soldiers of the National Reserve Forces.